The genus Tuponia Reuter, 1875 in Romania, with two new synonymies (Heteroptera: Miridae) - Carapezza, Attilio; Rădac, Ioan Alexandru (Zootaxa, 2021)
Based on recently collected material and on type specimens deposited in the collections of Muzeul de Istorie Naturală “Grigore Antipa”, Bucharest, Romania, and of the Zoologische Museum, Universität Hamburg, Germany, the following new synonymies are proposed: Tuponia (Chlorotuponia) prasina (Fieber, 1864) = Tuponia (Chlorotuponia) linnavuorii Wagner, 1961, syn. n.; Tuponia (Tuponia) montandoni Reuter, 1899 = Tuponia (Tuponia) macedonica Wagner, 1957, syn. n. Lectotype and paralectotype are designated for Tuponia (Tuponia) montandoni Reuter, 1899. Tuponia (Chlorotuponia) hippophaes (Fieber, 1861), Tuponia (Tuponia) arcufera Reuter, 1879 and Tuponia (Tuponia) elegans (Jakovlev, 1867) are recorded for the first time from Romania. Habitus images, drawings of male genitalia and identification key are provided for all Tuponia species recorded in Romania and the surrounding countries.